The Role of Dividend Policy in Moderating the Effect of Tax Planning and Investment Decisions on Firm Value - Arianti, Baiq Fitri; Angela, Ivana (Gorontalo Accounting Journal, 2026)
. The purpose of this research is to determine whether there is an effect of tax planning and investment decisions on firm value with dividend policy as a moderating variable in primary consumer goods sector companies listed on the Indonesia Stock Exchange in 2019-2023. The type of data used in this research is secondary data with data sources originating from the Indonesian Stock Exchange during the 2019-2023 period. The population of this research was 118 companies and the samples were 23 companies through purposive sampling. The data analysis methods used in this research are descriptive statistics, panel data regression analysis, classical assumption testing, and hypothesis testing. The results of this research indicate that Tax Planning does not have a significant effect on firm Value, while investment decisions have a significant effect on firm value, and dividend policy is unable to moderate tax planning and investment decisions on firm value.